2021
DOI: 10.21776/ub.ijhn.2021.008.01.7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge Determinants among Undergraduate Students in Selected University in Jakarta

Abstract: <p><em>Malnutrition problem (under and over nutrition), known as the double burden of malnutrition, was a growing concern in developing countries, including Indonesia. The 2018 Indonesia Basic Health Survey noted a substantial increase in the proportion of these nutritional impairments. As a fundamental factor of malnutrition, nutritional knowledge was expected to be occupied not only by vulnerable groups. A transitional age group like youth, in this case undergraduate students, should also be on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Statistical analysis was conducted using SPSS ver. 25 12,15,16,17 The level of nutritional literacy of the respondents in this study was dominated by the level of adequate nutritional literacy.…”
Section: Discussionmentioning
confidence: 86%
“…Statistical analysis was conducted using SPSS ver. 25 12,15,16,17 The level of nutritional literacy of the respondents in this study was dominated by the level of adequate nutritional literacy.…”
Section: Discussionmentioning
confidence: 86%
“…6 Another study in Indonesia, specifically in Jakarta, demonstrated that more than 30% of undergraduate medical students were categorised as overnutrition either being overweight or obese. 7 Nevertheless, undernutrition is also a problem that could not be overlooked, as macronutrients and micronutrients are needed by every organ in the human body. A low intake of nutrients, which leads to a low nutritional status, could cause disturbances in organ function, either in the gastrointestinal, cardiorespiratory, muscular, or even immune systems, and it could have a psychosocial effect.…”
Section: Introductionmentioning
confidence: 99%